German Exchange Rate Exposure at DAX and Aggregate Level, International Trade, and the Role of Exchange Rate Adjustment Costs - Gösta Jamin; Horst Entorf (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2004)
This article analyses value changes of German stock market companies in response to movements of the US dollar. The approach followed in this work extends the standard means of measuring exchange rate exposure in several ways (e.g. by using multi-factor modelling instead of augmented CAPM, application of moving window panel regressions, orthogonalization of overall market risk vis-?-vis currency risk). The main innovation lies in testing implications of exchange rate adjustment costs (hedging costs) for firm values and exposure. Based on time series data of German DAX companies, DM/ dollar rates and macroeconomic factors, we find a rather unstable, time-variant exposure of German stock market companies. Dollar sensitivity is positively affected by the ratio of exports/GDP and negatively affected by imports/GDP as well as by significant deviations of the dollar price from its long-run median. The first two findings are in line with the presumption that exporting corporations benefit from dollar price increases, whereas importing corporations benefit from dollar price decreases. The last finding can be explained by higher exchange rate adjustment costs in case of substantial deviations from the long-run median level. Furthermore, there is indication of asymmetric adjustment costs as effects from appreciations of domestic currency appear to be smaller than from depreciations.
Keywords: C23; G15; F31; 330; Börsenkurs; Wechselkursrisiko; US-Dollar; Aussenwirtschaft; Hedging; Kosten; Schätzung; Deutschland